Autonomia e dignidade nas relações privadas : uma reflexão em Kant e Rawls - Vilar, Érika Cristhina Nobre (2015)
This is a study which aims to promote a reflection about human dignity as the foundation of fundamentals rights, geared, specifically, to its effectiveness in the spheres of legal relations of a private nature. The relevance of the issue lies in the absence of dogmatic about the effectiveness of this fundamental value in the private sphere, the reigning absolute indeterminacy that often promotes the commitment of its axiological content. The aim of this study was to delimit, through a historical analysis, philosophical hermeneutics and the dignity of the human person, which values should prevail in its implementation, especially in the private sector. The development of this work was made possible by means of literature, involving legal and philosophical doctrine on the subject. During the study, we had the opportunity to investigate the origins of Private Law, examine the acquisition of rights by the person subject to status, to distinguish between freedom of choice and personal autonomy, analyze the intersection between private law and fundamental rights, as well as establishing an evolutionary historical overview of human dignity, as well as their philosophic elements from Kant and Rawls to define the ethical parameters that should condition its effectiveness among individuals. As a result of the research, we concluded that the realization of human dignity in the context of private legal relations, is not subject to specific parameters, especially those who assign the rights holders in the exercise of autonomy to assume an ethical commitment to dignity.